2014
DOI: 10.1099/mic.0.075317-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to abiotic surface induces SOS response in Escherichia coli K-12 strains under aerobic and anaerobic conditions

Abstract: During the colonization of surfaces, Escherichia coli bacteria often encounter DNA-damaging agents and these agents can induce several defence mechanisms. Base excision repair (BER) is dedicated to the repair of oxidative DNA damage caused by reactive oxygen species (ROS) generated by chemical and physical agents or by metabolism. In this work, we have evaluated whether the interaction with an abiotic surface by mutants derived from E. coli K-12 deficient in some enzymes that are part of BER causes DNA damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Concomitantly, in the present study yhj N coding for cellulose synthase regulator protein was up regulated where as in ABU strains of E. coli genes involved in cellulose synthesis ( bcs ABZC and bcs EFGgenes) were down regulated [43]. Genes encoding colanic acid synthesis ( wca L and wca M) were down regulated in the ocular E. coli and ABU strains [43] probably because expression of colanic acid inhibits the biofilm ability of E. coli [57]. Further in ocular E. coli L-1216/2010 colicin protecting conserved protein encoding genes cbr B and cbr C are up regulated by 11- and 288-folds respectively compared to the non-biofilm forming cells.…”
Section: Discussionmentioning
confidence: 66%
“…Concomitantly, in the present study yhj N coding for cellulose synthase regulator protein was up regulated where as in ABU strains of E. coli genes involved in cellulose synthesis ( bcs ABZC and bcs EFGgenes) were down regulated [43]. Genes encoding colanic acid synthesis ( wca L and wca M) were down regulated in the ocular E. coli and ABU strains [43] probably because expression of colanic acid inhibits the biofilm ability of E. coli [57]. Further in ocular E. coli L-1216/2010 colicin protecting conserved protein encoding genes cbr B and cbr C are up regulated by 11- and 288-folds respectively compared to the non-biofilm forming cells.…”
Section: Discussionmentioning
confidence: 66%
“…The SOS pathway is initiated through the activation of RecA, which in turn induces autocatalytic cleavage of the LexA repressor and induces the SOS response genes ( 8 , 10 ). RecA is involved in DNA repair, recombination, induction of the SOS response, horizontal gene transfer, and biofilm formation ( 10 , 12 14 ). Systematically altering bacterial SOS activity, both constitutive SOS activation and inactivation, has been revealed as a therapeutic strategy for potentiating bactericidal antibiotics like quinolones against highly susceptible wild-type E. coli ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, UPEC cells did not filament in host cells defective for pathogen recognition suggesting that filamentation is a regulated response to an active innate host response. It has also been observed that E. coli forms filaments when adhering to certain abiotic surfaces, which was proposed to be a result of DNA damage, possibly caused by damaging agents present on the surface (Costa et al, 2014). It is also well known that antibiotics induce cell filamentation.…”
Section: Bacterial Filamentation As a Stress Responsementioning
confidence: 98%